How should we prepare ourselves for new normal related to stopped competitions? Public health and athletes - Memari, A.; Shariat, A.; Cleland, J. A. (Iran Journal of Public Health, 2020)
Covid-19 has disrupted normal life not only among the general population and their daily ac-tivities, but also in different professions. Recrea-tional and elite athletes have been ordered to halt their exercise activities. Currently there is no social physical activity or professional competitions, thus there will be huge financial consequences related to stopping those activities. Athletes will lose their physical and emotional fitness and sponsors could potentially lose their business (1-3). What will be the new normal? What happens when athletes can do their training exercises at in home or indoor gyms or stadiums and sponsors can sell their tickets? Nevertheless, we do not know how long we must wait for this new nor-mal life and what we can do now?